Plant health improvement by Bacillus subtilis strain GBO3 in tomato against bacterial spot disease - P. HARIPRASAD, S. UMESHA* (Indian Phytopathology, 2010)
Seed bacterization with Bacillus subtilis strain GBO3 showed increased plant growth and reduced the bacterial leaf spot in tomato. Seedlings raised from seeds bacterized with GBO3 showed increased root length, shoot length, fresh weight and dry weight. The activity of phenylalanine ammonia-lyase (PAL) and polyphenol oxidase (PPO) were found increased in plants raised from bacterized seeds and reached their peak at 48 hours after pathogen inoculation (hpi). Similarly, phenolics accumulation was reached their peak at 96 hpi. The rate of reduction in the bacterial spot disease incidence in plants raised from bacterized seeds was directly proportional to the increased levels of PAL, PPO and phenol contents.